2015
DOI: 10.6004/jnccn.2015.0008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Guideline Treatment Nonadherence and the Impact on Survival in Patients With Colorectal Cancer

Abstract: Although medically justifiable reasons exist for deviating from NCCN Guidelines when treating patients with colorectal cancer (CRC), those who received nonadherent treatment had much higher risks of death, especially in the first year after diagnosis. This study's results highlight the importance of cancer health services research to drive quality improvement efforts in cancer care for patients with CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 33 publications
6
37
3
1
Order By: Relevance
“…The majority of patients received on-pathway and guideline recommended regimens during the first-line setting, although adherence dropped with subsequent lines. Other studies that have retrospectively evaluated adherence to guidelines or pathways for colorectal cancer have reported adherence rates to the initial primary therapy only, with reported adherence rates of 83% [5] [9]. Our study results of 88% and 84% adherence in the first line setting to NCCN guidelines and the US Oncology pathways respectively are consistent with that previously reported in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of patients received on-pathway and guideline recommended regimens during the first-line setting, although adherence dropped with subsequent lines. Other studies that have retrospectively evaluated adherence to guidelines or pathways for colorectal cancer have reported adherence rates to the initial primary therapy only, with reported adherence rates of 83% [5] [9]. Our study results of 88% and 84% adherence in the first line setting to NCCN guidelines and the US Oncology pathways respectively are consistent with that previously reported in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…10 Population and institutional studies have shown that adjuvant therapy may confer a survival advantage in some patients with resected colon cancer (eg, those with stage III or high-risk stage II disease). [11][12][13][14] Furthermore, randomized controlled trials have shown that the addition of oxaliplatin to these adjuvant regimens benefits some patients. [15][16][17][18][19] However, adjuvant treatment, especially with regimens containing oxaliplatin, is associated with considerable toxicity (notably chemotherapyinduced peripheral neuropathy), 16,20 and not all patients derive benefit.…”
Section: Risk Stratification and Adjuvant Treatment For Stage III Colmentioning
confidence: 99%
“…After examining the probability and frequency of emergency care utilization presented by other variables, we found that the deterioration of health conditions, such as advanced cancer staging and increase in outpatient visits and inpatient visits, increases the probability and frequency of emergency care utilization and there were significant differences among groups, which is consistent with the results of many studies on survival of patients with colorectal cancer. [11,32,33] Some studies suggested that patients with advanced colorectal cancer received the best quality of overall treatment with MDT, [34,35] which means that with the advance of colorectal cancer, the challenges to diagnosis, treatment and care would be greater. We hope to see more investigators dedicate their research in this area in the future.…”
Section: Discussionmentioning
confidence: 99%